Do Men Matter to Female Competition Even When They Don't? - Erica G. Birk; Logan M. Lee; Glen R. Waddell (Institute for the Study of Labor (IZA), 2016)
A large literature attempts to identify factors that contribute to gender differences in performance and in the decision to compete. We exploit a highly competitive environment in which elite-female athletes are exposed to the presence of men without the element of direct competition, which allows for the identification of psychological effects of competition. Our results suggest that the presence of men affects the performance of female runners differentially across ability, with negative performance effects being concentrated among lower-ability runners.
Keywords: J16; D01; D03; 330; competition; competitiveness; athlete; gender